Pelatihan Microsoft Access Dalam Pembuatan Aplikasi Penjualan Barang Di SMK UISU Pematangsiantar - Dedek Indra Gunawan Hts; Deny Adhar (Jurnal Pengabdian Ahmad Yani, 2021)
UISU Islamic Private Vocational School is one of the private vocational schools in Pematangsiantar city. In the curriculum, this vocational school teaches computer subjects as part of its vocational specifications. With advances in technology, almost everyone already has their own computer. So many schools began to make computer learning as one of the subjects or majors taught at the school. One example is making an application for selling goods. There are many benefits to be gained, if you can prepare financial statements. These benefits such as knowing information about product goods, stock of goods and the results of the sale of goods. Being one of the ingredients in making decisions to find out the results of selling goods based on hassle or reports, business actors will know how many products were sold in 1 period. Here the author volunteered to hold Microsoft Access Training in Making Goods Sales Applications for UISU Islamic Private High School students as a community service program.